Epigenome-wide association study of diabetic chronic kidney disease progression in the Korean population: the KNOW-CKD study - Hye Youn Sung; Sangjun Lee; Miyeun Han; Woo Ju An; Hyunjin Ryu; Eunjeong Kang; Yong Seek Park; Seung Eun Lee; Curie Ahn; Kook-Hwan Oh; Sue K. Park; Jung-Hyuck Ahn (Scientific Reports, 2023)
Abstract Since the etiology of diabetic chronic kidney disease (CKD) is multifactorial, studies on DNA methylation for kidney function deterioration have rarely been performed despite the need for an epigenetic approach. Therefore, this study aimed to identify epigenetic markers associated with CKD progression based on the decline in the estimated glomerular filtration rate in diabetic CKD in Korea. An epigenome-wide association study was performed using whole blood samples from 180 CKD recruited from the KNOW-CKD cohort. Pyrosequencing was also performed on 133 CKD participants as an external replication analysis. Functional analyses, including the analysis of disease-gene networks, reactome pathways, and protein–protein interaction networks, were conducted to identify the biological mechanisms of CpG sites. A phenome-wide association study was performed to determine the associations between CpG sites and other phenotypes. Two epigenetic markers, cg10297223 on AGTR1 and cg02990553 on KRT28 indicated a potential association with diabetic CKD progression. Based on the functional analyses, other phenotypes (blood pressure and cardiac arrhythmia for AGTR1) and biological pathways (keratinization and cornified envelope for KRT28) related to CKD were also identified. This study suggests a potential association between the cg10297223 and cg02990553 and the progression of diabetic CKD in Koreans. Nevertheless, further validation is needed through additional studies.